Evaluation of the physical and chemical quality and trace elements of water in Cupatitzio River, Michoacán - Mendoza-Mora, Felipe; Cruz Cárdenas , Gustavo; Silva, José Teodoro; Ochoa-Estrada, Salvador; Ãlvarez-Bernal, Dioselina (Tecnología y ciencias del agua, 2023)
In Mexico, around 90 % of the rivers are polluted mainly from wastewater resulting in human health issues. This work is aimed at determining the water quality of Cupatitzio River; 20 sampling sites (SS) were determined in rainy (August 2016) and dry (May 2017) seasons; 31 trace elements (TE) were obtained and 15 physicochemical parameters; three quality indices were calculated: Water Quality Index (WQI), Pollution Index (IC) and the Canadian Council of Ministers of the Environment, Water Quality Index ( ). Statistical analysis was conducted to associate variables. Results show for the rainy season, the quality indices indicates that the worst quality is found in the middle watershed due to the wastewater and leachate from a landfill; in the dry season, low quality reaches the low watershed. High concentrations of Fe, Al and P trace elements are found in the middle and lower watershed. It is worth mentioning that they may be associated with the pesticides used in avocado orchards. Finally, analyses show an association between poor quality, low dissolved oxygen and the presence of reservoirs. Therefore, the river water is not fit for human use and consumption.